ANALISIS KESEHATAN BANK DI INDONESIA BERDASARKAN RISK BASED BANK RATING SELAMA DAN SETELAH PANDEMI COVID-19 - Nursasi, Enggar; Wijaya, Christabel Devina Eva Wijaya; Hariadi, Sugeng; Andiani, Lidia (Inspirasi Ekonomi : Jurnal Ekonomi Manajemen, 2024)
This research aims to determine the health of banks in Indonesia during and after the Covid- 19 pandemic. The data source used in this research is secondary data in the form of financial reports of banking companies listed on the Indonesia Stock Exchange in 2020-2022. To assess the health of banks in this research, a risk assessment approach or Risk Based Bank Rating (RBRR) was used by reviewing the components of the Risk Profile, Good Corporate Governance, Earnings, and Capital (RGEC) of banking companies. The results of the research show that the health of state-owned banks during the pandemic was declared healthy and after the Covid-19 pandemic was declared very healthy, while the health of National Private Banks during and after the Covid-19 pandemic was declared healthy considering that several banks were in the "Less Healthy" position. The Covid-19 pandemic significantly affects Return On Assets (ROA).